Kasus Langka Pseudoaneurisma Arteri Radial Pasca Angiografi Koroner - Laksono, Sidhi; Kusharsamita, Hillary (Majalah Kedokteran Indonesia, 2024)
Introduction: Radial artery pseudoaneurysm is a rare but potentially severe complication that may occur after coronary angiography. Although uncommon, promptly identifying and addressing the issue is crucial to avoid further complications. Case Report: Here, we describe the case of a 65-year-old female patient who developed a radial artery pseudoaneurysm after undergoing coronary angiography to evaluate her chest discomfort. The diagnosis of a pseudoaneurysm was confirmed by Doppler ultrasonography, which identified a swirling flow pattern. Persistent pain symptoms and ineffective conservative treatment necessitated surgery.Case Discussion: This case highlights the importance of vigilance in identifying rare complications such as radial artery pseudoaneurysm following coronary angiography. Conclusion: Prompt diagnosis and appropriate management strategies, including surgical intervention, when necessary, are crucial for optimal patient outcomes.